Eat move sleep how small choices lead to big changes - Rath, Tom 1975- ([Arlington, Virginia] Missionday, 2013)
#1 "New York Times" bestselling author Tom Rath delivers a book that will improve your health for years to come in three of interconnected areas: eating, moving, and sleeping --
Quietly managing a serious illness for more than 20 years, Rath has assembled a wide range of information on the impact of eating, moving, and sleeping. He offers advice that will help you make good decisions automatically, in all three of these interconnected areas. With every bite you take, you will make better choices. You will move a lot more than you do today. And you will sleep better than you have in years --
The basics -- Small adjustments -- Quality first -- Break the cycle -- Staying healthy -- What counts -- Refined fuel -- Timing matters -- Shortcuts -- Decisions -- Working -- Quitting -- Myth busting -- Home -- Get ahead -- Energy -- Expectations -- Good nights -- Think again -- Your routine -- Simple steps -- Looking good -- An extra boost -- Reminders -- Prevention -- Daily choices -- New habits -- Trend setters -- Ideas for life -- Wrapping up -- Concluding thoughts -- First 30 days challenge.
Includes bibliographical references (pages 219-244).
Keywords: Exercise; Food habits; Health behavior; Sleep